Dissipative analysis and synthesis for uncertain discrete-time control and signal processing systems - Tan, Zhi Qiang (2009)
This thesis examines the dissipative analysis and synthesis for discrete-time control and signal processing systems with and without uncertainties. In particular, we focus on the notion of quadratic dissipativity. The thesis contains two main parts.